Impact of buying behavior of youth towards cosmetic products in Perambalur Town - Krishna Raj, Prof. Venkata; Geetha, Prof. R. (IJRDO - Journal of Business Management, 2017)
The purpose of this study is to investigate internal and external influences on consumers purchasing decisions on cosmetic products perambalur in Tamilnadu. The questionnaires were given to 125 consumers who are all using cosmetics. Out of 125 consumers contacted, 75 questionnaires were received with required coverage and details. The instruments of this study involved two parts: the first section of the instrument consisted of forced-choice questions about demographic characteristics: gender, marital status, age, occupation, monthly income level. The second section variables chosen for this study in order to measure the influence of consumer buying behaviour in cosmetics products. The Statistical Package for the Social Science (SPSS) for Microsoft Windows 20.00 was used to complete the analysis of the collected data. Descriptive statistics, including means, standard deviations were implemented in order to investigate the demographic data, one-way analysis of variance (ANOVA) were used to determine whether any significant relationships exist among respondents. In addition, the .05 level of statistical significance was set at all statistical tests in the present study. The findings of the study were generalized as follows: Statistically significant differences were found in Income level by the different brand dimensions like social, culture and there is no statistically significant difference in dimension of Personal and psychological. In the end of the study implications and conclusion were provided. Index